Selective anticancer effects of Serjania marginata Casar. extract in gastric cells are mediated by antioxidant response. Issue 8 (22nd April 2021) - Serpeloni, Juliana Mara; Specian, Ana Flavia Leal; Ribeiro, Diego Luis; Tuttis, Katiuska; Heredia‐Vieira, Silvia Cristina; Vilegas, Wagner; Martínez‐López, Wilner; Varanda, Eliana Aparecida; de Syllos Cólus, Ilce Mara
Abstract: Gastric cancer is the fifth most common malignancy worldwide. Serjania marginata Casar. (SM) displays anti‐inflammatory properties and has been used to treat gastrointestinal disorders. In the current study, we examined whether the hydroethanolic extract of SM leaves exerted cytotoxic, mutagenic, and protective effects in non‐tumor gastric epithelium cells (MNP01) and gastric adenocarcinoma cells (ACP02) in vitro and analyzed whether its action was selective. Initially, cell viability (MTT assay), cell cycle kinetics (flow cytometry), and cell proliferation (total protein content) were analyzed. In addition, genomic instability (cytokinesis‐block micronucleus cytome assay), anti/pro‐oxidant status (CM‐H2 DCFDA probe), and transcriptional expression (RT‐qPCR) of genes related to cell cycle, cell death, and antioxidant defense were also evaluated. The SM extract was cytotoxic toward MNP01 and ACP02 cells at concentrations greater than 300 and 100 μg·ml −1, respectively, and decreased protein content only toward ACP02 cells at 200 μg ml −1 . In ACP02 cells, the SM extract at 100 μg·ml −1 associated with doxorubicin (DXR; 0.2 μg ml −1 ) clearly promoted cell cycle arrest at the G2/M phase. The extract alone was not mutagenic to either cell type and reversed DXR‐induced DNA damage and H2 O2 ‐induced oxidative stress in MNP01 cells. The gene expression experiments showed that SM hydroethanolic extract exerts an antioxidant response via NFE2L2 activation in non‐tumor gastric cells, and cell cycle arrest (G2/M) in ACP02 gastric cancer cells via the TP53 pathway. The selective action of SM indicates that it is a promising therapeutic agent to treat gastric diseases and merits further studies. Abstract : Serjania marginata Casar. (SM) extract was cytotoxic toward MNP01 (300 μg·ml −1 ) and ACP02 gastric cells (100 μg·ml −1 ). In ACP02 cells, the SM extract (100 μg·ml −1 ) associated with doxorubicin (DXR; 0.2 μg ml −1 ) promoted cell cycle arrest at the G2/M phase. SM extract was not mutagenic and reversed DNA damage and oxidative stress in MNP01 cells. SM extract exerts an antioxidant response via NFE2L2 activation in MNP01 cells, and cell cycle arrest (G2/M) in ACP02 cells via the TP53 pathway.